The Role of Mixed Marriage Organizations in the Processing of Residence Permits for Foreign Nationals - Agustin, Reza; Fuad Attamimi, Zeehan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to explain the role of mixed marriage organizations in the process of obtaining residence permits for foreign nationals. This research uses the normative juridical method, with data obtained from the identification and clarification of legal facts from mixed marriage organizations. In recent years, population migration between countries has continued to increase. Along with the times, more and more foreign nationals choose to live in Indonesia, one of which is due to mixed marriages. A mixed marriage is a marriage between two individuals who are subject to different legal systems in Indonesia, usually due to differences in citizenship, where one of the spouses is an Indonesian citizen. Foreign nationals married to Indonesian citizens are required to apply for a residence permit in Indonesia, such as a permanent residence permit (ITAP). To obtain an ITAP, the applicable requirements must be met according to the purpose of the application. This process includes applying for a status change from a limited stay permit (ITAS) for family unification to a permanent residence permit (ITAP). The Mixed Marriage Organization plays an important role in helping to resolve the various issues faced by families in mixed marriages. The organization carries out its activities through three main pillars: Advocacy, Socialization, and Consultation. This topic was chosen by the author because it has not been discussed in previous articles.